2022
DOI: 10.1371/journal.pone.0268432
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, underweight, malignancy and a marked catabolic state as predictors for worse outcomes in COVID-19 patients with moderate-to-severe disease admitted to Internal Medicine Unit

Abstract: Introduction During COVID-19 pandemic, Internal Medicine Units (IMUs) accounted for about 70% of patients hospitalized. Although a large body of data has been published regarding the so-called first wave of the pandemic, little is known about the characteristics and predictors of worse outcomes of patients managed in IMUs during the second wave. Methods We prospectively assessed demographics, comorbidities, treatment and outcomes, including ventilation support (VS) and death, in patients admitted to our IMU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…According to the literature, during the social isolation period imposed in response to the COVID-19 pandemic, remarkable alterations occurred both in terms of food habits and healthy behaviors, which are associated with increased body weight [ 50 , 51 ]. Both alterations in body weight and circulating urea levels are considered to predictors of worse outcomes in COVID-19 patients, particularly in the older adult population [ 50 , 51 , 52 ]. Therefore, although we did not observe significant alterations in body weight and urea levels between the pre- and post-COVID-19 pandemic period s, for the first time, we demonstrated that two important risk factors for COVID-19 are positively correlated in a group of older women who interrupted their regular practice of exercise training during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, during the social isolation period imposed in response to the COVID-19 pandemic, remarkable alterations occurred both in terms of food habits and healthy behaviors, which are associated with increased body weight [ 50 , 51 ]. Both alterations in body weight and circulating urea levels are considered to predictors of worse outcomes in COVID-19 patients, particularly in the older adult population [ 50 , 51 , 52 ]. Therefore, although we did not observe significant alterations in body weight and urea levels between the pre- and post-COVID-19 pandemic period s, for the first time, we demonstrated that two important risk factors for COVID-19 are positively correlated in a group of older women who interrupted their regular practice of exercise training during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans and animal models suggest that being in identical conditions of social isolation can lead to both weight gain and an inflammatory phenotype in adipocyte adipose tissue and weight loss [28][29][30] and, in vulnerable groups (adolescents, and people with post-traumatic stress), an increase in the adoption of unhealthy weight-control practices [31,32]. Resulting excess or deficiency of body weight is dangerous for clinical COVID-19 outcomes, increasing the risk of severe disease course, hospitalisation, and death [33][34][35][36][37][38][39][40]. With the metabolic tissue burden induced by weight gain and adipose tissue dysfunction exacerbating the inflammation caused by SARS-CoV-2 virus contributing to systemic chronic inflammation of low-grade malignancy, overexpression of ACE2 receptors in obesity may support infection and act as a reservoir for the virus [41][42][43] and comorbidities (including atherogenic dyslipidaemia, hypertension, cardiovascular disease, and type 2 diabetes) further impair organ and system function, thereby worsening the course of infection [42,44].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] In our previous study, we have found that not only age and malignancies, but underweight and inflammation levels as well were predictors of worse outcomes (death or mechanical ventilation). [ 10 ]…”
mentioning
confidence: 99%
“…inflammation levels as well were predictors of worse outcomes (death or mechanical ventilation). [10] However, little is known about the clinical characteristics and the outcomes of patients hospitalized in Internal Medicine in this new context of mass vaccination and predominance of new viral variants.…”
mentioning
confidence: 99%